Pemodelan Benda Uji Balok Kayu Laminasi Komposit Duren-Sengon. - Ratna Widyawati (Rekayasa : Jurnal Ilmiah Fakultas Teknik Universitas Lampung, 2010)
Structural modeling nowadays is mostly done on the testing in the laboratory because they viewed the results are very helpful in the field of research, design and scientific development. Modeling the structure of many done in making samples for the very complex structure, both in geometry and structure of the boundary conditions. Modelling composite wood beam specimen duren-sengon is to make laminated wood beam specimen (glulam beam) using a scale model, because all this research on laminated wood beams (glulam beam) always use the test object prototype. In this paper we will discuss about how to calculate scale model of laminated wood beams so that the behavior of the model scale specimens will be made in accordance with the behavior of a prototype test object. The steps of the test object modeling of composite laminated wood beams duren-sengon is to create model structures using the True Model. Because of the True Model similarity met all the requirements or have complete similarity. There are 10 (ten) types of physical variables involved in the modeling calculations include loads (F), span (l), deflection (δ), moment of inertia (I), stiffness (K), modulus of elasticity (E), stress (σ) , bending moment (M), beam width (b) and high beam (h). Specified length of span (l) and modulus of elasticity (E) as independent variable. The calculation of test object modeling laminated wood beams produced eight formulations that can be used to make a scale model test object. Eight formulations can be used to calculate the value of the load (F), deflection (δ), moment of inertia (I), stiffness (K), stress (σ), bending moment (M), beam width (b) and high beam (h ) of the test object model scale to be made, by first setting the value for the long span (l) and modulus of elasticity (E) as independent variables.